2009
DOI: 10.1007/s10529-009-0165-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular activation of NF-κB, pro-inflammatory mediators, and signal pathways in γ-irradiated mice

Abstract: The effects of gamma-irradiation on inflammatory gene expression, including NF-kappaB activation, in the kidney of C57/BL6 mice exposed to 1-9 Gy doses of (60)Co gamma-irradiation. Radiation enhanced the NF-kappaB activation and oxidative stress caused a dose-dependent disruption in the redox balance. The significance of this study is the new molecular information gained on gamma-irradiation effects through the activation of pro-inflammatory genes by NF-kappaB via the MAPK signaling pathway. Considering the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…For example, irradiation has been shown to increase oxidative stress, which activates inflammatory functions such as those governed by NF-kB signaling and the AP-1 complex. 38, 39 Genes involved in the transcription factor regulation of immune components, such as those associated with NF-kB, were identified as differentially expressed in haNK cells by irradiation exposure. It has been shown that irradiation of the parent NK-92 cells halted their proliferation while both cytotoxicity and immune signaling functions remained intact.…”
Section: Discussionmentioning
confidence: 99%
“…For example, irradiation has been shown to increase oxidative stress, which activates inflammatory functions such as those governed by NF-kB signaling and the AP-1 complex. 38, 39 Genes involved in the transcription factor regulation of immune components, such as those associated with NF-kB, were identified as differentially expressed in haNK cells by irradiation exposure. It has been shown that irradiation of the parent NK-92 cells halted their proliferation while both cytotoxicity and immune signaling functions remained intact.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance in ROS/iron metabolism are the facts that NF-κB is redox-sensitive (e.g. Aggarwal and Sung 2009; Baeuerle and Henkel 1994; Chandrasekaran and Taylor 2008; Cho et al 1998; Dröge 2002; Fulda et al 2010; Galaris et al 2008; Gloire et al 2006; Gloire and Piette 2009; Ha et al 2010; Haddad et al 2000; Hayashi et al 1993; Janssen-Heininger et al 2008; Lagan et al 2008; Lukosz et al 2010; Nishi et al 2002; Phillips et al 2010; Schreck et al 1991, 1992; Schreck and Baeuerle 1994; Sen and Packer 1996; She et al 2002; Surh et al 2005; Surh and Na 2008; Thannickal and Fanburg 2000; Trachootham et al 2008, 2009; Valko et al 2007; Weinberg and Chandel 2009; Wondrak 2009; Xiong et al 2003) and that there are links between NF-κB and NGAL/lcn2 (Bu et al 2006; Cowland et al 2003, 2006, 2008; Karlsen et al 2010) and/or hepcidin (Sow et al 2009; Tacchini et al 2008). Specificity is likely to come, in part, via the frequency encoding of NF-κB activity (Ashall et al 2009; Nelson et al 2004).…”
Section: Inflammation and Nf-κbmentioning
confidence: 99%
“…Damaging effects of IR are generally mediated through the production of reactive species (RS), and a substantial increase in RS levels induces cellular damage and decrease in antioxidant enzymes, as well as activates intracellular signaling pathways that activate the expression of many inflammatory genes. The IR induced molecular responses may also be characterized as increased cyclooxygenase-2 (COX-2) level, inducible nitric oxide synthase (iNOS) and vascular adhesion molecule-1 (VCAM-1) expressions that also initiates the activation of the transcription factor NF-κB 266 . The key role played by NF-κB activation in the process of inflammation has been reported to be closely associated with a redox-sensitive signal cascade that includes MAPKs (ERK, c-Jun Nterminal kinase (JNK] and p38) and Akt 266,267 .…”
Section: Radiation Countermeasures In Relation To Nf-mentioning
confidence: 99%
“…The IR induced molecular responses may also be characterized as increased cyclooxygenase-2 (COX-2) level, inducible nitric oxide synthase (iNOS) and vascular adhesion molecule-1 (VCAM-1) expressions that also initiates the activation of the transcription factor NF-κB 266 . The key role played by NF-κB activation in the process of inflammation has been reported to be closely associated with a redox-sensitive signal cascade that includes MAPKs (ERK, c-Jun Nterminal kinase (JNK] and p38) and Akt 266,267 . However, activation of the Akt signaling pathway has been known to reduce forkhead box-O (FOXO) transcription activity 268 , and is involved in cytoprotective effects against oxidative stress 269 .…”
Section: Radiation Countermeasures In Relation To Nf-mentioning
confidence: 99%